More trees for more water in drylands: myths and opportunities - Sheil, D.; Bargués Tobella, A. (2020)
The mechanisms by which trees influence water availability remain incompletely understood, but the last two decades have brought astonishing advances. We already know enough to see major opportunities to improve water security in tropical drylands through tree cover, while also yielding the many other benefits that trees provide.